Anti-Bacterial evaluation of 1,3-Benzodioxole derived imidazolium and pyridinium based ionic liquids - Sagar Panchal; Hitesh Sehrawat; Nisha Yadav; Shipra Chandra; Vivek Mishra; Neera Sharma; Ramesh Chandra (Journal of Ionic Liquids)
1,3-benzodioxole is one prominent biological active moiety which is abundant in numerous natural products. In this work we have synthesized 1,3-benzodioxole based ionic liquids using the different fluorides and have evaluated their anti-bacterial properties on Gram negative (-) Escherichia coli and Gram positive (+) Staphylococcus aureus bacterial strains were assessed. In this report we have reported the MIC (minimum inhibitor concentration) and ZOI (zone of inhibition) analysis of the different combinations and the best combination was the further used for the in-silico computational study for the interaction at the atomic level.